Determinan Kualitas Tidur Remaja Menurut Social Cognitive Theory Model : Tinjauan Pustaka Tahun 2020-2025 - Muhammad Adithya Sasmitha; Luqman Effendi (Jurnal Ventilator, 2025)
Background: Sleep disorders in adolescents are a significant health problem, with a global prevalence reaching 57.8% and particularly high rates in several cities in Indonesia. Poor sleep quality negatively impacts physical health, such as the risk of cardiovascular disease and anemia, as well as mental and cognitive health. Sleep behavior is influenced by a dynamic interaction between personal and environmental factors, as explained in Social Cognitive Theory (SCT). Research Objective: To identify the determinants of sleep deprivation in adolescents, specifically individual and environmental factors, based on a Social Cognitive Theory (SCT) perspective through a literature review from 2019 to 2025. Method: This study utilized a literature review. To obtain research data, the authors searched for scientific articles through Google Scholar, PubMed, and ScienceDirect databases, then analyzed 10 articles that met the inclusion criteria, published between 2020 and 2025. Results: Factors significantly associated with adolescent sleep quality were identified, with individual factors being the most dominant determinant (found in 7 studies), including academic stress and smartphone addiction. Furthermore, a positive association was found with environmental factors (found in 4 studies), such as bright lighting, noise, and uncomfortable room temperature. Conclusion: Within the framework of Social Cognitive Theory, adolescent sleep quality is the result of a reciprocal interaction between personal factors (perceived stress and self-control over gadgets), the physical environment, and sleep behavior. Individual factors such as stress and nighttime gadget use reduce self-efficacy for regular sleep, which is exacerbated by an unfavorable environment.